Predicting electrical power generation from photovoltaic panel - Wee, Yun Nee; Mohamad Nor, Ahmad Fateh (Penerbit UTHM, 2020)
As years pass by, renewable power is generating billions in economic activity with continuous and rapid growth which begins to provide on the guarantee of a clean energy future. Renewable energy, usually referred as “clean energy” is defined as the electrical energy that is being generated from the natural sources or processes that can be replenished. The most common renewable energy includes wind, PV, geothermal, biomass, and hydropower. PV or photovoltaic (PV) cells are made from silicon or other materials that convert sunlight directly into electricity [1], [2]. In Malaysia, distributed PV systems generate electricity evenly and locally for buildings, homes, farms and businesses either through rooftop panels or community projects that power entire neighborhoods. One of the advantages of PV energy is that it has the least negative impact on the environment compared to any other energy sources. It does not produce greenhouse gases and does not pollute the air and water. Moreover, generating own electricity means that there will be less usage from the utility supplier. This will immediately contribute to savings on energy bills. Plus, investment can be made by selling the unused electricity back to the grid, Tenaga Nasional Berhad (TNB) under the Feed in Tarif (FiT) program that has been included in the 10th Malaysia Plan...